Fostering links, building trust, and facilitating change: connectivity helps sustain longitudinal integrated clerkships in small rural and remote communities - Brendan Carrigan; William MacAskill; Janani Pinidiyapathirage; Sherrilyn Walters; Lara Fuller; Kay Brumpton (BMC Medical Education)
Abstract Background Maldistribution of medical professionals presents a significant challenge globally and leads to inequitable healthcare access, particularly in remote areas. Longitudinal integrated clerkships (LICs) in rural areas can improve workforce distribution and may be an innovative contributor to solving maldistribution issues. However, to align with healthcare needs, LICs must be sustainable in small communities, which often have a limited medical workforce. This study investigates the key elements underpinning LIC sustainability in small communities. Methods This study adopted a constructivist research paradigm in which participants’ constructions of their experiences supporting LICs in small rural communities were explored. Participants were conveniently sampled from the LIC community of practice attending the 2021 virtual annual conference of the Consortium of Longitudinal Integrated Clerkships. Data were collected through video recording and thematically analysed to identify barriers and enablers to running sustainable LIC programmes. Results Eleven participants fulfilling key roles within LICs, including clinical school directors, program coordinators, and clinical educators, were recruited for the study. Thematic analysis indicated that it is Connectivity, expressed through three subthemes, Fostering Links, Building Trust, and Facilitating Change, which underpins sustainable LICs in small communities. Conclusions Connectivity is a strong mediator for sustainability of LICs and may be the central defining theme of LICs. Increasing connectivity through prioritizing community engagement, trust-building, and strategic investment enhances the sustainability of rural LICs, ensuring their continued positive contribution to medical workforce distribution in underserved areas.